2014
DOI: 10.4067/s0301-732x2014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la reactividad conductual frente al manejo y su relación con el Cortisol sanguíneo, contusiones y pH de la carne en novillos

Abstract: Caracterización de la reactividad conductual frente al manejo y su relación con el cortisol sanguíneo, contusiones y pH de la carne en novillos # Characterisation of behavioural reactivity in steers during handling and its relationship with blood cortisol, bruising and meat pH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It was found that cortisol ( p < .0001), dopamine ( p <.02), and noradrenaline ( p < .01) levels were significantly higher in the religiously slaughtered animal group, which led the authors to conclude that meat quality was affected by religious slaughter practices. Moreover, in another study where the capacity of behavioral tests to predict the incidence of DC was tested, a moderate correlation ( r = 0.34; p < .05) between on‐farm cortisol levels and crush test scores (indicating behavior of the animal) was observed, while an excellent correlation between the behavior test and pHu ( r = 0.81‐0.87; p < .01) was observed, indicating merit in combining physiological measurements with behavior observations (De Freslon et al., 2014). Interestingly, high (∼15)‐fold changes in cortisol levels have been observed between baseline and response levels in saliva (Dzviti et al., 2019; Negrão et al., 2004).…”
Section: Potential Markersmentioning
confidence: 99%
“…It was found that cortisol ( p < .0001), dopamine ( p <.02), and noradrenaline ( p < .01) levels were significantly higher in the religiously slaughtered animal group, which led the authors to conclude that meat quality was affected by religious slaughter practices. Moreover, in another study where the capacity of behavioral tests to predict the incidence of DC was tested, a moderate correlation ( r = 0.34; p < .05) between on‐farm cortisol levels and crush test scores (indicating behavior of the animal) was observed, while an excellent correlation between the behavior test and pHu ( r = 0.81‐0.87; p < .01) was observed, indicating merit in combining physiological measurements with behavior observations (De Freslon et al., 2014). Interestingly, high (∼15)‐fold changes in cortisol levels have been observed between baseline and response levels in saliva (Dzviti et al., 2019; Negrão et al., 2004).…”
Section: Potential Markersmentioning
confidence: 99%